Nanosilica supplementation in tomato increases oviposition on stems and caterpillar mortality in the tomato pinworm - Kokou R. Fiaboe; Fathiya M. Khamis; Xavier Cheseto; Abdullahi A. Yusuf; Baldwyn Torto (Proceedings of the National Academy of Sciences, 2025)
Silicon-induced responses play a key role in plant defense against herbivory, though the underlying mechanisms remain underexplored. In this study, we examined how mesoporous silica nanoparticles (MSNs) affect tomato ( Solanum lycopersicum ) defense against an invasive and highly destructive lepidopteran herbivore, the tomato pinworm (TPW), Phthorimaea absoluta . In tomato plants supplemented with MSN, prior exposure to TPW oviposition shifted subsequent egg-laying from a preference for leaves to an even distribution between stems and leaves. This shift was not observed in nonsilicon-supplemented plants. Prolonged oviposition triggered pigmentation in the basal cells of type I glandular trichomes on the stems of silicon-supplemented plants. Chemical analysis by coupled gas chromatography-mass spectrometry revealed that the pigmented trichome was rich in soluble sugars (sucrose and l -arabinose) and waxes, dominated by the saturated hydrocarbon tetracosane. Bioassays with the crude extract of the pigmented trichome and a three-component sugar–wax blend replicated the oviposition and caterpillar response observed with the pigmented trichome, while individual components produced variable effects. While l -arabinose alone replicated the oviposition effects of the three-component sugar–wax blend, sucrose increased oviposition and caterpillar feeding and survival, while l -arabinose and tetracosane caused the highest caterpillar mortality. Additionally, these treatments altered caterpillar gut microbiota composition and influenced frass volatiles, which attracted the TPW natural enemies, Nesidiocoris tenuis (predator) and Neochrysocharis formosa (parasitoid). Our findings suggest that silicon supplementation increases tomato defense against TPW through oviposition-induced responses, which promotes recruitment of natural enemies.